An application of integration approaches for archaeo‐geophysical data: Case study from Aizanoi. Issue 1 (24th September 2017) - Küçükdemirci, Melda; Özer, Elif; Piro, Salvatore; Baydemir, Niyazi; Zamuner, Daniela
Abstract: Transforming multi‐dimensional datasets, containing measurements of different physical parameters recorded at the same location, into a single composite imagery is quite important and frequently used in geophysical analysis as well as other scientific disciplines. This study focuses on the application of several different integration approaches for archaeo‐geophysical data with a purpose of achieving complementary and improved information about the buried archaeological target by generating a single data set from multiple geophysical methods. An extensive geophysical survey using ground penetrating radar (GPR) and differential magnetic methods was made in different parts of the Aizanoi archaeological site (Cavdarhisar, Kutahya, Turkey) to locate and enhance subsurface archaeological structures. However, in this article, the outputs of graphical, mathematical and statistical integration approaches, which are applied both on synthetic images and real field case data, are presented and discussed. Comparing these results and experimental applications, mathematical and statistical integration approaches provide more useful and practicable information than just the single distinct datasets from each geophysical parameter studied.